Peningkatan Impulse Buying Mahasiswa di Semarang terhadap Produk Fashion Lokal melalui Ethnocentrisme, Brand Image dan Country of Origin (COO) - Sri Widiyati; Saiful Ghozi (Faculty of Economic and Business, 2018)
Improvement of Impulse Buying Students in Semarang on Local Fashion Products Through Ethnocentrism, Brand Image, and Country of Origin (COO)Impulse buying is a very interesting phenomenon for retailers and marketers because it is the biggest market share and occupy a very important position and can increase sales. The aim of the research is to analyze whether the Country of Origin ( COC), brand image and ethnocentrism significantly affect students impulse buying of local fashion in Semarang city. Data analysis used in this research is linier regression analysis. The result shows that COO the only variables that do not significantly affect students impulse buying. Need a strategy of brand image reinforcement and promotion emphasized on the love of domestic products. Promotion of products at the local level of Semarang city needs to be improved by taking into account the values of excellence and local wisdom.DOI: 10.15408/ess.v8i1.6979